ANALISIS KEBUTUHAN PERANGKAT LUNAK MENGGUNAKAN ANALISIS FAKTOR PADA PROGRAM STUDI ILMU KEPERAWATAN UNDIP - Eko Handoyo; Adnan Setiawan AR (Diponegoro University, 2009)
The need to obtain the speed and information accuracy provided in an organization conducting dataprocessing in gross, complex and finite during make the organization require the information system tosupport their business.Systems analysis represent the early stage in determining quality of system development in informationsystem to be developed. Analysis of Requirement of sistem, one of the phase of systems analysis, haveplaying important role to formulate what must be owned and done by an information system.This report using quistioner of the measuring instrument by using modification of Likert scale for onehundred responder to get the data. Processing data is conducting bytest of validity and reability, thenfactor analysis is done for formulation of system requirement.